EVALUASI WAKTU TUNGGU PELAYANAN RESEP PASIEN RAWAT JALAN DI RUMAH SAKIT ANWAR MEDIKA - Erviani Dinda Mahmudah Sari; Khurin In Wahyuni; Puspita Raras Anindita (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2021)
The waiting time for finished drug service is the grace period from the time the patient submits the prescription until receiving the finished drug with a minimum standard set by the Ministry of Health is â‰¤ 30 minutes, while the waiting time for concoction drug service is the grace period from the time the patient submits the prescription until receiving the concoction drug that is â‰¤ 60 minutes. This study aims to determine the average waiting time for outpatient prescription services at Anwar Medika Hospital. This research was conducted with a cross sectional descriptive method. Primary data was collected through direct observation and recording of prescription service waiting times in the waiting time recording form on February 10, 2020 to February 11, 2020. Data taken were 384 outpatient prescriptions consisting of 346 non-concoctions and 38 prescription concoctions. In this study, 384 recipes were used as the research sample consisting of 346 for non-concoction recipes and 38 for recipe concoctions. The average time needed to complete a non-concoction recipe is 18.7 minutes and the time required to complete a recipe concoction is 30.9 minutes. Based on the results of research that has been done, it is found that the average waiting time for prescription services at Anwar Medika Hospital has fulfilled the requirements according to the minimum service standards at the hospital.